The end of low interest rates? - Markus Demary (Institut der deutschen Wirtschaft (IW), 2017)
After the economic recovery has strengthened and inflation rates have increased, hopes for higher interest rates emerged among savers, while debtors began to fear higher financing costs. This article argues, that there is room for higher interest rates, but this room is small compared to historical interest rate levels.
Keywords: 330